Aktivitas Antioksidan Pada Buah, Tepung, dan Biskuit Berbasis Labu Siam (Sechium edule) - Fajriani Fajriani; Jamaludin Sakung (Universitas Tadulako, 2023)
Chayote or Sechium edule is one of Indonesia's plants and is a potential food commodity to be used as the main ingredient for product development, chayote is a plant that lives in tropical and sub-tropical areas. This study aims to determine the antioxidant content of fruit, flour and chayote biscuits using UV-Vis spectrophotometry. Analysis of the antioxidant content in this research is using the DPPH method (1,1-diphenyl-2-picrylhydrazil) as a source of free radicals. Fruit extract, flour and chayote biscuits were analyzed for their antioxidant content with various concentrations of 20 ppm, 40 ppm, 60 ppm, 80 ppm, 100 ppm. The results obtained that raw chayote fruit extract has a very weak antioxidant content with an average IC50 value of 256,723 ppm, chayote flour has a moderate antioxidant content with an average value of IC50 140,999 and chayote biscuits has a weak antioxidant content with the average value of IC50 is 179.619 ppm